2014
DOI: 10.1002/j.0022-0337.2014.78.1.tb05663.x
|View full text |Cite
|
Sign up to set email alerts
|

Community–Based Dental Education and Dentists’ Attitudes and Behavior Concerning Patients from Underserved Populations

Abstract: Marita R. Inglehart, Dr. phil. habil.Abstract: The objectives of this study were to explore how dentists with well-structured vs. not well-structured communitybased dental education (CBDE) experiences differ in perceptions of their CBDE and its impact on their professional lives and in their professional attitudes and behavior related to treating patients from underserved populations. The relationships between CBDE evaluations and impact on the dentists' professional lives and professional attitudes and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 25 publications
1
36
0
1
Order By: Relevance
“…Nevertheless, the consistently positive correlations between preparedness and personal value hint that students may find worthwhile what they feel prepared to do. Similarly, Rohra et al found that students' participation in high‐quality, community‐anchored educational activities positively affected their attitudes about treating vulnerable populations 31 . This finding may have more to do with increased confidence than population exposure, especially for patients with special health needs, for whom additional training is particularly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the consistently positive correlations between preparedness and personal value hint that students may find worthwhile what they feel prepared to do. Similarly, Rohra et al found that students' participation in high‐quality, community‐anchored educational activities positively affected their attitudes about treating vulnerable populations 31 . This finding may have more to do with increased confidence than population exposure, especially for patients with special health needs, for whom additional training is particularly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Those who had more positive views about the DEC's location reported that they would be more likely to return and practice there in the future. However, contrary to historical research (18,(27)(28)(29) most students in this study would prefer to return home or close to friends and family.…”
Section: Discussionmentioning
confidence: 57%
“…In this 'hub and spoke' model, the dental school in Preston acts as a 'hub' and the DECs as 'spokes'. As students treating patients in under-served communities are more likely to treat such populations after graduating (5,17), and are reported to have more positive professional attitudes and behaviours regarding those patients (18), one hope of this model was that students, having had experience of treating patients in these areas of high need, would be more likely to opt to remain in these localities after completing their training (15). However, it was acknowledged that this would be dependent to some extent on student rankings in the DF1 recruitment process, which determine to which region a graduate is allocated (19).…”
Section: Local Contextmentioning
confidence: 99%
“…The revised curriculum embraced the themes of community service, academics, and citizenship . Dental students with structured community‐based dental education programs were found to have better overall patient/provider outcomes than dental students with less‐structured community‐based dental education programs . The complementary clinical training enhances students’ confidence in their abilities and time management skills.…”
Section: Discussionmentioning
confidence: 99%